The Role of Islamic Boarding Schools in Enhancing the Quality of Religious Education in Indonesia: A Perspective on the Transformation of Islamic Education - Sofwan Manaf; Rokimin; Asrul Hanafiah Mokhsen (NAJAHA, 2026)
Islamic boarding schools (pesantren) have historically served as the cornerstone of religious education in Indonesia, yet their capacity to enhance educational quality amid globalization and technological advancement remains insufficiently examined. This study investigates the role of pesantren in improving the quality of religious education through the lens of Islamic education transformation. Employing a qualitative approach with a multiple case study design, data were collected through semi-structured interviews with 24 informants, participatory observation, and document analysis across six pesantren in Java and Sumatra representing traditional (salafiyah), modern (khalafiyah), and integrated typologies. The findings reveal three principal dimensions of transformation: first, curriculum integration that harmonizes classical Islamic texts (kitab kuning) with contemporary scientific and vocational competencies; second, pedagogical modernization through the adoption of student-centered learning methods and digital technology while preserving the core values of character formation (tarbiyah); and third, institutional governance reform characterized by strategic leadership of kiai, quality assurance mechanisms, and community-based partnerships. The study concludes that pesantren that successfully balance the preservation of traditional religious identity with adaptive innovation (al-muhafazhah 'ala al-qadim al-shalih wa al-akhdzu bi al-jadid al-ashlah) demonstrate significantly enhanced educational outcomes. These findings contribute to the theoretical discourse on Islamic education management by proposing a triadic transformation model and offer practical implications for policymakers and pesantren administrators seeking to strengthen religious education quality in Indonesia.